2018
DOI: 10.1097/md.0000000000011766
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous expulsion of a huge cervical leiomyoma from the vagina after cesarean

Abstract: Rationale:As more and more women delay their child bearing age, the prevalence of uterine fibroids during pregnancy is likely to increase.Patient Concerns & Lessons:We report a Chinese Tibetan case with spontaneous expulsion of a huge cervical myoma after cesarean. Decreased blood supply of the myoma and the uterine contraction may contribute to the spontaneous expulsion. Vaginal-myomectomy is recommended as the initial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…8 Our patient reported bleeding, pain, and the sensation of a mass being eliminated via the vagina. This is similar to the study published by Zhang et al 5 who reported that common symptoms of fibroid degeneration and expulsion included vaginal bleeding, fever, and the sensation of a mass being eliminated by the vagina along with smelly discharge. Most often myomatous degeneration is associated with pain.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…8 Our patient reported bleeding, pain, and the sensation of a mass being eliminated via the vagina. This is similar to the study published by Zhang et al 5 who reported that common symptoms of fibroid degeneration and expulsion included vaginal bleeding, fever, and the sensation of a mass being eliminated by the vagina along with smelly discharge. Most often myomatous degeneration is associated with pain.…”
Section: Discussionsupporting
confidence: 90%
“…3 Among the few published cases reports of spontaneous expulsion of fibroids, some occurred during the pregnancypuerperium cycle, but most were seen following magnetic resonance-guided focused ultrasound, use of drugs, or uterine artery embolization. [4][5][6] The mechanism of spontaneous fibroid degeneration and expulsion is not clear. Degeneration could occur due to excessive fibroid growth leading to a decrease in blood supply and this excessive growth could also compress the irrigating arteries of the fibroids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 81 studies were subsequently excluded after the examination of the abstract and full text: 29 manuscripts were excluded because only the abstract was retrieved, 24 as they did not have English language and 28 because they did not have an adequate population and intervention. Definitively, 38 articles were included in our systematic review ( Figure 1 ) [ 3 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Data synthesis was available in Table 1 and Table 2 .…”
Section: Resultsmentioning
confidence: 99%